Formulation, charcterization and in-vitro evalution of floating microspheres of nateglinide - HIMANSU BHUSAN SAMAL; SUDDHASATTYA DEY; DHIRAJ KUMAR; D SANDEEP KUMAR; S.A.SREENIVAS; V. RAHUL (International Journal of Pharma and Bio Sciences, 2011)
The present study involves design and characterization of floating microspheres with Nateglinide as model drug for prolongation of gastric residence time. Nateglinide Floating Microspheres were prepared by w/o/o emulsification solvent diffusion technique using rate controlling polymers ethyl cellulose and hydroxy propyl methyl cellulose. The shape and surface morphology of prepared microspheres were characterized by optical and scanning electron microscopy respectively. FTIR analyses the absences of drug-polymer interaction. In vitro drug release studies were performed and drug release kinetics was evaluated using the linear regression method. Effects of polymer concentration, solvent composition, particle size, drug entrapment efficiency and drug release were also observed. The prepared microspheres exhibited prolonged drug release (more than 12 h) and remained buoyant for > 24 h. The mean particle size increased and the drug release rate decreased at higher polymer concentration. In vitro studies demonstrated diffusion- controlled drug release from the microspheres.